Programmable light‐driven soft actuator enabled by structurally anisotropic liquid crystalline network - Zhaoping Deng; Xinyu Chen; Xinrui Deng; Jiangmin Yang; Shuai Zhou; Jingyu Chen; Peixiang Wang; Huai Yang; Ruochen Lan (Aggregate)
Abstract The design and fabrication of advanced soft actuators with programmable actuation are highly desirable in constructing intelligent soft robots. In this work, a programmable light‐driven liquid crystalline network (LCN)‐based soft actuator was judiciously designed and prepared by constructing structural anisotropy across the thickness of the film. A three‐dimensional (3D) deformable LCN actuator was realized by polymerization‐induced phase separation of small‐molar‐weight monomers and polymer networks. The resultant anisotropic LCN displays anisotropic microscale nanoporous architecture across the thickness in addition to uniform alignment at the molecular scale. The actuation behaviors of LCN film are tunable by adjusting the size and distribution of nanopores in LCN bulk via changing polymerization conditions and monomer components. More importantly, the nanoporous LCN film can be harnessed as a promising template to achieve diverse light responsiveness by changing the photothermal dyes via a feasible washing and refilling process, demonstrating a reprogrammable light‐driven soft actuator.